UK Services for dairying industries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The United Kingdom Dairy Association (UKDA) represents the scientific, technological, educational, and commercial organisations of the UK dairy production and processing industries. It offers services to countries developing their dairying...